Resistance to kinase inhibition through shortened target engagement. (31st December 2022) - Rangwala, Aziz M.; Berger, Benedict-Tilman; Robers, Matthew B.; Knapp, Stefan; Seeliger, Markus A.
ABSTRACT: Imatinib, a selective inhibitor of the breakpoint cluster region (BCR)-ABL kinase, is the poster child for targeted cancer therapeutics. However, its efficacy is limited by resistance mutations. Using a quantitative bioluminescence resonance energy transfer assay in living cells, we identified ABL kinase mutations that could cause imatinib resistance by altering drug residence time.